Elements of industrial hazards : health, safety, environment and loss prevention - Tatiya, Ratan Raj (CRC Press/Balkema, 2011)
"An introductory course on Health, Safety and Environment as applicable to all manufacturing and exploration engineering industries. Its first part deals with fundamentals, ecology and environmental engineering and covers air and water pollution sources, magnitude, measuring techniques and remedial measures to minimize them. The second part deals with industrial hazards, health and safety. It includes standards, strategies, risk assessment and accident analysis. The last part treats eight elements of HSE management, which is currently a critical activity for virtually any engineering business. Intended for a wide audience active in the engineering, ranging form the plant supervisor to HSE consultants to operators in the field"--